Inclusive Play: Defining Elements of Playful Teaching and Learning in Culturally and Linguistically Diverse ECEC - Jonna Kangas; Anna-Leena Lastikka; Outi Arvola (MDPI AG, 2023)
Inclusive values are integral to early childhood education and care (ECEC) policies, promoting equal participation opportunities and individual support for all children. Play serves as a method for meaningful engagement, mutual cultural knowledge creation, and learning within ECEC. Pedagogical play entails teachers' observation, interaction, support, and guidance. This study investigates practical elements and methods employed by teaching staff and experienced by children during playful activities. Conducted as a case study in two culturally diverse ECEC centers during spring 2023, data collection involved video-recorded monitoring of children's daily activities in five groups. Video data were transcribed and analyzed using content analysis tools to identify categories of inclusive play. Findings are presented as narratives to honor children's experiences. The study identifies five elements of inclusive play: teachers' active participation and presence, balanced repetition with flexible plans and adaptive goals, playful language fostering joy in play, non-verbal and kinesthetic communication with enabling tools, and emerging play marked by interaction and lasting intensity. These elements reveal opportunities and challenges for children's inclusion and learning approaches, informing recommendations for promoting inclusive play in ECEC. Inclusive play emphasizes diverse strategies accommodating differences in learning styles and modes of knowledge expression among teaching staff and children.